RESPON PEMBUNGAAN TURNERA SUBULATA TERHADAP INTENSITAS PENYINARAN DAN MACAM PUPUK P - Umi Kusumastuti Rusmarini; Lilik Eko Mardiyanto (AGROISTA : Jurnal Agroteknologi, 2021)
Turnera subulata is a benefit plant for oil palm, the flower is habitat for enemy of oil palm insect. This study aims to know the response of Turnera subulata flowering on light intensity and different kinds of phosphor fertilizers. The research was conducted in STIPER Agricultural Institute Yogyakarta. The research used split plot design as experimental method with two factors. The first factor is light intensity which is consisted of 3 levels: 54,9 fc; 20,4 fc; and 9,8 fc. The second factor is the type of phosphor fertilizers: TSP, SP36, Gandasil B, and Control. The results are analysed with Variance and Duncan’s Multiple Range Test, 5% significance. The research showed that there is interaction effect between light intensity and phosphor fertilizer which is resulted in the amount of flower and flower age of Turnera subulata. Application of 54,9 fc light intensity combined with Gandasil B fertilizers give the best response for the amount, age, and also growth of Turnera subulata. Keywords: Turnera subulata, light intensity, Gandasil B, TSP, SP36